Structural and Electrical Properties of TiO2 Thin Film Derived from Sol-gel Method using Titanium (IV) Butoxide - Senain, Isrihetty; Nayan, Nafarizal; Saim, Hashim (International Journal of Integrated Engineering, 2010)
Fabrication of titanium dioxide (TiO2) thin film on microscope glass using sol-gel method has been studied intensively. The starting materials were titanium (IV) butoxide, ethanol, acetic acid, triton x-100, hydrochloric acid and deionized water. The materials were mixed together to form the sols. Then, the heat and ageing treatment was applied to form stable sols. The sols were then spin coated on the glass substrate to form the homogenous and transparent TiO2 thin film. The TiO2 thin film was coated at several layers using specific conditions. To evaluate the performance of thin film, the crystallinity of the thin film was determined by using the x-ray diffractometer  (XRD). The change on the surface morphology was observed using atomic force microscope (AFM). The electrical property of the thin film was determined by doing the current-voltage (I-V) analysis on the thin film. It has been successfully shown that the anatase crystalline phase was observed when the TiO2 thin film was heated at 500°C. The roughness and the crystalline phase of TiO2 thin film changed drastically with the growth conditions. Finally, the effect of film preparation to the film resistivity also showed a critical aspect where we should take into account during the preparation of TiO2 thin film.